Translation: Inspirations We Live by - Piotrowska, Maria (2022)
The main aim of the book is not only a historical and contemporary overview of translation research models and methods but also the author’s critical analysis of the state of the art in Translation Studies and a commentary of the progress of the discipline; as indicated in the chapter titles, which are called “Reflections.” The monograph is structured around seven major areas of reflection upon translation and the field of multi-dimensional translation research, and its particular chapters concern chronologically: translation metaphors, historical perspectives on translation, translation – culture interrelations, with particular focus on ethnography of translation; translator competence, translator’s decision-making and intuition. The last chapter offers “a map of Translation Studies”, which demonstrates its dynamism, diversity, complexity, inter- and multidisciplinarity. The palimpsest metaphor that concludes translation reflections and refers back to the first chapter, defines translation as a complex sequence of experiential layers and inspirations “we live by”, as indicated in the title of the classic of cognitive linguistics by Lakoff and Johnson (1980), which the monograph title alludes to.
Keywords: ethnography of translation; history of translation; intuition; metaphor; palimpsest; translator competence; translator’s decision-making; translation research; Translation Studies